Effect of an interleukin-4 variant on late phase asthmatic response to allergen challenge in asthmatic patients: results of two phase 2a studies - Wenzel, Sally; Wilbraham, Darren; Fuller, Rick; Getz, Elise Burmeister; Longphre, Malinda (The Lancet (British edition), 2007)
Increases in T helper (Th) 2 cytokine concentrations have been seen in atopic asthma, with interleukin 4 and interleukin 13 thought to have a role in the physiological response to allergen challenge. Our aim was to assess the therapeutic effect of pitrakinra, an interleukin-4 variant that targets allergic Th2 inflammation by potently inhibiting the binding of interleukin 4 and interleukin 13 to interleukin-4Rα receptor complexes. In two independent randomised, double-blind, placebo-controlled, parallel group phase 2a clinical trials, patients with atopic asthma were treated with pitrakinra or placebo via two routes. In study 1, patients were randomly assigned to receive either 25 mg pitrakinra (n=12) or placebo (n=12) by subcutaneous injection once daily. In study 2, patients were randomly assigned to receive either 60 mg pitrakinra (n=16) or placebo (n=16) by nebulisation twice daily. Inhaled allergen challenge was done before and after 4 weeks of treatment. The primary endpoint for study 1 was maximum percentage decrease in forced expiratory volume in 1 s (FEV 1) over 4–10 h after allergen challenge, whereas that in study 2 was average percentage decrease in FEV 1 over 4–10 h after allergen challenge. All patients except those with baseline data only were included in our analyses. These trials are registered with ClinicalTrials.gov, numbers NCT00535028 and NCT00535031. No patients dropped out or were lost to follow-up in study 1; in study 2, two patients in the placebo group and one in the pitrakinra group dropped out or were lost to follow-up. These individuals had baseline data only, and were excluded from the analyses. In study 1, there was a 17·1% maximum percentage decrease in FEV 1 in the pitrakinra group; by contrast, the maximum decrease was 23·1% in the placebo group (difference 6%, 95% CI −4·37 to 16·32; p=0·243). In study 2, there was a 4·4% average percentage decrease in FEV 1 in the pitrakinra group; by contrast, the average percentage decrease was 15·9% in the placebo group (3·7 [95% CI 2·08–6·25] times lower in the pitrakinra group; p=0·0001). There were fewer asthma-related adverse events (p=0·069) and fewer adverse events requiring β-agonist rescue (p=0·031) after subcutaneous administration of pitrakinra than with placebo. There were too few asthma-related adverse events in study 2 to assess the effect of inhalation of pitrakinra on adverse events. Local treatment, targeted at inhibition of interleukins 4 and 13 in the lung, could substantially diminish the symptoms of asthma.